Analisis Faktor Minat Belajar Geografi Jurusan IPS di MAN 1 Probolinggo - Roby Firmandil Diharjo; Syamsunardi Syamsunardi (LaGeografia, 2023)
Learning continues to be applied to increase student knowledge. Learning strategies are ways to attract students' attention to education. Students who have an interest in education will get a more conducive and active learning atmosphere. The purpose of this study was to find out one of the factors of students' interest in geography subjects majoring in social studies. The method used in this research is descriptive qualitative. Subjects who were targeted in data collection were students majoring in social studies. The results of the research show that students who are interested in taking geography subjects are optimistic because the lessons are carried out full of creativity. Students respond better to each geography subject given by the teacher. The teacher provides creativity that makes students interested in following the lesson. Teacher professionalism is important in attracting students' interest in learning and making the learning atmosphere more enjoyable. This description becomes a reference for the future, education should have a lot of creativity, not only focusing on a theory but collaborating with practicum. The amount of literacy from teachers in managing learning in class will generate interest in student learning, especially in all subjectsAbstrakBelajar terus di terapkan guna peningkatan pengetahuan siswa. Strategi belajar adalah cara dilakukan untuk menarik perhatian siswa di dalam pembelajaran. Siswa yang memiliki minat belajar akan mendapatkan suasan belajar lebih kondusif dan aktif. Tujuan dari penelitian ini untuk mengetahui salah satu faktor minat peserta didik terhadap mata pelajaran geografi jurusan IPS. Metode yang di gunakan dalam penelitian ini berupa deskriiptif kualitatif. Subyek yang menjad sasaran dalam pengambilan data adalah siswa jurusan IPS. Hasil penelitian di dapat bahwasannya siswa yang minat mengikuti mata pelajaran geografi bersifat postif di karenakan pelajaran di laksanakan penuh dengan kreativitas. Siswa lebih merespon baik setiap mata pelajaran geografi yang di berikan oleh guru. Guru memberikan kreativitas yang menjadikan siswa minat mengikuti pelajaran. Profesionalitas guru berperan penting untuk menarik perhatian minat belajar siswa dan membuat suasana belajar lebih menyenangkan. Gambaran ini menjadi rujukan untuk masa yang akan datang seharusnya pembelajaran memiliki banyak kreatifitas bukan hanya berfokus pada sebuah teori melainkan mengkolaborasikan dengan praktikum. Banyaknya literasi dari guru dalam mengatur pembelajaran di kelas akan menghasilkan minat belajar siswa khususnya semua mata pelajaran.